Leading information systems academic teams to high performance - Varajão, João (2018)
Information Systems (IS) projects are creative processes implemented by teams. To succeed, such projects require teams to perform at their best. A way to tackle this challenge is to enhance the human resources potential through team leadership. High-performing teams have been studied for some years. However, little has been written about academic IS projects and on how to lead teams to high performance. Building upon Thamhain's (2004) recommendations to lead teams to high performance, our primary aim was to investigate the influence of these recommendations on IS project teams' performance in an academic environment. Twenty-eight teams of masters students involved in the development of academic IS projects were invited to participate in our study. Results regarding the correlation between Thamhain's (2004) recommendations and project teams' performance of IS students are given and analyzed. We also discuss the implications of these recommendations on enhancing academic IS project teams' performance.